Best practices for teaching with emerging technologies - Pacansky-Brock, Michelle; Ko, Susan Schor (New York, NY : Routledge, 2013)
'As social media and Web 2.0 technologies continue to transform the learning trends and preferences of students, educators need to understand the applicability of these new tools in all types of learning environments. Best Practices for Teaching with Emerging Technologies will provide both new and experienced online, hybrid, and face-to-face instructors with: Practical examples of how low-cost and free technologies can be used to support student learning Best practices for integrating web-based tools into a course management system and managing student privacy in a Web 2.0 environment'Showcase' spotlights woven throughout the book, providing examples of how the tools described in the book are already being used effectively in educational settings An easy-to-reference format, organized with visual icons used to delineate each tool's visual, video, voice, and mobile features Ideas for integrating mobile learning into your students' learning experiences This practical, easy-to-use guide will serve the needs of both 2- and 4-year college educators seeking to refresh or transform their instruction. Readers will be rewarded with an ample yet manageable collection of proven emerging technologies that can be leveraged for generating content, enhancing communications with and between students, and cultivating participatory, student-centered learning activities'--
'Best Practices for Teaching with Emerging Technologies is a practical, easy-to-use guide that provides both 2- and 4-year college educators seeking to refresh or transform their instruction'--
Includes bibliographical references and index.
Keywords: Educational technology